Mapping the Risks Assessing the Homeland Security Implications of Publicly Available Geospatial Information - Baker, John C. (RAND Corporation, 2004)
Following the attacks of September 11, 2001, many agencies within the federal government began restricting some of their publicly available geospatial data and information from such sources as the World Wide Web. As time passes, however, decisionmakers have begun to ask whether and how such information specifically helps potential attackers, including terrorists, to select U.S. homeland sites and prepare for better attacks. The research detailed in this book aims to assist decisionmakers tasked with the responsibility of choosing which geospatial information to make available and which to restrict.